Meningkatkan Kemampuan Bersosialisasi Anak Melalui Permainan Tradisional Kelereng ( PTK Di PAUD Sinar Kungkai Kabupaten Seluma) - Engriani, Ezi; Margaretha, Lydia; Asnawati, Asnawati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine the improvement in children's socialisation skills through traditional marbles games at the Sinar Kungkai Early Childhood Education Centre in Seluma Regency. This study was a classroom action research (CAR) study using a cyclical procedure. The subjects of this study were 11 children in Group B at the Sinar Kungkai Early Childhood Education Centre. The research was conducted over two cycles, each consisting of two meetings. Data analysis was performed using both qualitative and quantitative descriptive methods, with the qualitative analysis focusing on determining the improvement in the process, expressed as a predicate, while the quantitative analysis was used to determine the improvement in outcomes using percentages. Based on the research results, the improvement in children's socialisation skills through traditional marbles games at PAUD Sinar Kungkai was 39.20% in Cycle I, Session I; 48.86% in Cycle I, Session II; 58.52% in Cycle II, Session I; and 80.68% in Cycle II, Session II. The conclusion of this study is that the use of traditional marbles games in learning can improve children's social skills at PAUD Sinar Kungkai in Seluma District, as evidenced by an increase in Cycle II, Session II, with a percentage achievement of 80.68%, meeting the criteria for ‘very good development’ (BSB).